Pragmatic Transfer in Indonesian ESL Refusal Strategies - Fiany Dhitasari (2012)
Language and culture are not separated, one cannot fully understand the nature either language or culture unless they are seen as inseparable. The problem is when the people from different cultures learn the other languages. Their second language (L2) will be influenced by their first language (L1). Thereby, this study is about pragmatic transfer in refusal strategies use which occurred to Indonesian ESL as nonnative English speakers. The study investigates about what kinds of refusal strategies used by Indonesian ESL which will be compared to American English native speakers and Indonesian native speakers. The data were collected by using a Discourse Completion Test (DCT). The DCT consists of twelve situations which are divided into four categories (requests, invitations, offers, and suggestions). The respondents have to response as if their social status was in lower, equal, and higher than the interlocutors. There are 20 kinds of refusal strategies used by respondents, and the most significance different strategy used is addressing term and regret strategies. The results show that pragmatic transfer does occur when Indonesian ESL learners use addressing term and regret strategies in lower social statuses.